IBM Cognos Framework Manager. - Curran, Terry (Packt Publishing, 2013)
Presented in a handson style, this guide presents you with real world examples to guide you through every process step by step. This book will be useful for any developer, novice or expert, who uses Framework Manager to build packages, but wants to expand their knowledge even further.